Proceso de atención de enfermería en gestante hipertensa de 35 semanas con anemia severa. - Zaldumbide Olalla, Selena Lisbeth (2021)
Hypertensive disorders during pregnancy are very frequent complications considered to be an important cause of maternal and / or fetal morbidity and mortality. Anemia in pregnant women constitutes a morbidity and mortality problem that affects both the mother and her child, and can cause complications both in the perinatal and postnatal stages. Anemia is a decrease in the hemoglobin concentration with a consequent reduction in the hematocrit value. Due to the difference in hemoglobin concentrations between men and women, and also in pregnant and non-pregnant women, so there are variations in the interval that defines anemia. There is sufficient evidence that iron deficiency anemia in pregnant women increases the risk of preterm birth and low birth weight. This clinical case presented below is intended to inform everyone about the great importance of pregnancy in people with anemia, since anemia affects the development of the fetus. Gestational hypertension constitutes a major public health problem and one of the main causes of maternal-neonatal mortality and complications such as cardiovascular, liver and kidney. For this reason, a clinical case of a 17-year-old female patient with a medical diagnosis of arterial hypertension is studied, who comes for an emergency accompanied by a relative. Through the analysis, the health problem of the patient was identified in order to improve medical and nursing management, which must be timely, based on a comprehensive assessment that ensures the maternal-fetal well-being, in such a way that they know the risk factors that can give rise to these pathologies and their possible complications.